Tanggung Jawab Pemegang Protokol Notaris Terhadap Gugatan Pemalsuan Akta Otentik - Rahayu, Yenny Rahmadiyanti; Rato, Dominikus; Ohoiwutun, Y.A Triana (Universitas Ekasakti, 2023)
In essence, a notary as a public official has the authority to make deeds authentic in accordance with norms, values ​​and provisions of laws and regulations applicable so that the law can work in society. Every deed made by the notary must be kept in the notary's protocol, and the protocol must be transferred in the case of the notary died or his term of office has expired or retired. The existence of a lawsuit addressed to the notary protocol holder regarding the forgery of authentic deeds that have been transferred to him will become a problem in the future. The notary who receives the protocol will still be summoned for information if there are problems related to the protocol in his control, because this is one of the responsibilities of the notary protocol recipient. Article 65 of the Notary's Position Law explains that a notary is responsible for every deed he makes even though the Notarial Protocol has been submitted and transferred to the party holding the Notarial Protocol. The notary holding the Protocol only has the obligation to care for and maintain the deed that has been submitted to him, and is not responsible for the contents of the deed. The storage of notary protocols as state archives is also not regulated in detail in the Notary Public Law. So there needs to be special arrangements regarding policies, guidance and management of notary protocols. In order to create legal certainty for notaries in storing and maintaining notary protocols.